TINGKAH LAKU MAKAN RUSA JAWA (CERVUS TIMORENSIS) YANG DIPELIHARA PADA LOKASI PENANGKARAN YANG BERBEDA - Deden Ismail (Bumi Lestari Journal of Environment, 2011)
The research carried out on Java deer (Cervus timorensis) at two captive sites are in Cariu Bogor regency, which is lowlands and Ranca Upas Bandung regency which is a plateau. Both these locations have the altitude, temperature and air humidity, rainfall and different maintenance management. Observation on this research from the morning until late afternoon, 12 hours a day (at 06.00 am until 18.00 pm) lasted for 6 months from November 2005-May 2006. The purpose of this study to determine the feeding behavior: a) time of grazing; b) the amount of pull grazing per minute; c) the amount of cud per minute in the two breeding sites by sex and age groups. The results showed that the timing of grazing in the paddock, Javan deer in Cariu have longer and highly significant difference (P <0.01) than in Ranca Upas. When compared to the number of pull grazing per minute Javanese deer in each age group adults, youth and fawn in Cariu with the Ranca Upas respectively are: 59.15 ± 6.70> 46.44 6.39 (P<0.01); 55.64 ± 6.02> 45.00 ± 6.40 (P <0.01); 58.55 ± 9.06> 43.50 ± 2.12 (P <0.05 .) While many Javan Deer cud per minute in each age group adults, youth and fawn in Cariu compared with Ranca Upas respectively are: 58.60 ± 4.14 <62.00 ± 3.62 (P <0 , 01); 52.69 ± 5.04 <59.00 ± 2.53 (P <0.05); 46.70 ± 1.70 <49.50 ± 0.71 (P <0.05). High distinction, quality and type of grass that is eaten Javan deer in Cariu and Ranca Upas cause differences of long grazing in the paddock , the number of pull grazing per minute and the number of cud per minute, besides feeding the cut and carry on a Javan deer in Cariu cause time grazing in the paddock at the Javan deer in Cariu shorter than the Javan deer in Ranca Upas.